2009
DOI: 10.1074/jbc.m805404200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nuclear-encoded Subunits of the Chloroplast NAD(P)H Dehydrogenase Complex

Abstract: The NAD(P)H dehydrogenase (NDH) complex functions in photosystem I cyclic electron transfer in higher plant chloroplasts and is crucial for plant responses to environmental stress. Chloroplast NDH complex is a close relative to cyanobacterial NDH-1L complex, and all fifteen subunits so far identified in NDH-1L have homologs in the chloroplast NDH complex. Here we report on the identification of two nuclear-encoded proteins NDH48 and NDH45 in higher plant chloroplasts and show their intimate association with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 37 publications
(17 reference statements)
4
58
1
Order By: Relevance
“…1C). So far, a total of 25 NDH subunits have been identified by various approaches (Rumeau et al, 2005;Ishihara et al, 2007;Ishikawa et al, 2008;Majeran et al, 2008;Shimizu et al, 2008;Peng et al, 2009;Sirpiö et al, 2009aSirpiö et al, , 2009bTakabayashi et al, 2009;Suorsa et al, 2010;Yabuta et al, 2010). If we assume that only one copy of each subunit is included in the complex, the calculated molecular mass of NDH is approximately 690 kD, which is almost identical to that of the NDH complex detected in lhca5 lhca6.…”
Section: Ndh Is Present As a Monomer In The Lhca5 Lhca6 Double Mutantmentioning
confidence: 53%
“…1C). So far, a total of 25 NDH subunits have been identified by various approaches (Rumeau et al, 2005;Ishihara et al, 2007;Ishikawa et al, 2008;Majeran et al, 2008;Shimizu et al, 2008;Peng et al, 2009;Sirpiö et al, 2009aSirpiö et al, , 2009bTakabayashi et al, 2009;Suorsa et al, 2010;Yabuta et al, 2010). If we assume that only one copy of each subunit is included in the complex, the calculated molecular mass of NDH is approximately 690 kD, which is almost identical to that of the NDH complex detected in lhca5 lhca6.…”
Section: Ndh Is Present As a Monomer In The Lhca5 Lhca6 Double Mutantmentioning
confidence: 53%
“…This approach has been extensively used to monitor NDH-CET activity in cyanobacteria Deng et al, 2003;Ma and Mi, 2005;Battchikova et al, 2011a;Dai et al, 2013;Zhang et al, 2014;Zhao et al, 2014) and higher plants (Burrows et al, 1998;Shikanai et al, 1998;Hashimoto et al, 2003;Wang et al, 2006;Peng et al, 2009Peng et al, , 2011bPeng et al, , 2012Sirpiö et al, 2009;Yamamoto et al, 2011;Armbruster et al, 2013). As shown in Figure 1B, the NDH-CET activity in both mutants was lower than that in the wild type as judged by the height and relative rate of postillumination increase in Chl fluorescence.…”
Section: Isolation Of Ndh-cet-defective Mutantsmentioning
confidence: 99%
“…Since it has been well established that the presence of all NDH subunits is required for the assembly and functioning of the complex (Rumeau et al, 2005;Ishihara et al, 2007;Shikanaï, 2007aShikanaï, , 2007bSirpiö et al, 2009;Takabayashi et al, 2009), the presence of the Ndh complex in the different genotypes was investigated using an anti-NDH-H (a different subunit of the Ndh complex) antiserum (Figure 4). Compared with the levels of the wild-type protein, the homozygous line retained <10 and 50% of the protein (NDH-H) in leaves and the immature green fruit, respectively ( Figures 4B and 4D).…”
Section: Orr Gene Expression and Subcellular Localization Of Its Corrmentioning
confidence: 99%
“…Several Arabidopsis mutants affected in these pathways have been studied (Munekage et al, 2002;Rumeau et al, 2005;Ishihara et al, 2007;Shikanaï, 2007a;DalCorso et al, 2008;Peng et al, 2009;Sirpiö et al, 2009;Takabayashi et al, 2009) and showed no change in their carotenoid content. However, participation of PQ redox state in carotenogenesis in other tissues than leaves cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%